The Professional Culture of Community Pharmacy and the Provision of MTM Services - Meagen M. Rosenthal; Erin R. Holmes (MDPI AG, 2018)
The integration of advanced pharmacy services into community pharmacy practice is not complete. According to implementation research understanding professional culture, as a part of context, may provide insights for accelerating this process. There are three objectives in this study. The first objective of this study was to validate an adapted version of an organizational culture measure in a sample of United States' (US) community pharmacists. The second objective was to examine potential relationships between the cultural factors identified using the validated instrument and a number of socialization and education variables. The third objective was to examine any relationships between the scores on the identified cultural factors and the provision of MTM services. This study was a cross-sectional online survey for community pharmacists in the southeastern US. The survey contained questions on socialization/education, respondents' self-reported provision of medication therapy management (MTM) services, and the organizational culture profile (OCP). Analyses included descriptive statistics, a principle components analysis (PCA), independent samples t-test, and multivariate ordinal regression. A total of 303 surveys were completed. The PCA revealed a six-factor structure: social responsibility, innovation, people orientation, competitiveness, attention to detail, and reward orientation. Further analysis revealed significant relationships between social responsibility and years in practice, and people orientation and attention to detail and pharmacists' training and practice setting. Significant positive relationships were observed between social responsibility, innovation, and competitiveness and the increased provision of MTM services. The significant relationships identified between the OCP factors and community pharmacist respondents' provision of MTM services provides an important starting point for developing interventions to improve the uptake of practice change opportunities.